HPB P63 Five-year follow-up after pancreatoduodenectomy performed for malignancy: a nine-year experience. (7th December 2022) - Russell, Thomas; Labib, Peter; Aroori, Somaiah
Abstract: Background: Pancreatic ductal adenocarcinoma (PDAC) of the pancreatic head is a leading cause of cancer-related death in the Western world and its incidence is set to rise across the globe. Unfortunately, the majority of patients present with metastatic disease and prognosis is very poor. Ampullary adenocarcinoma (AA) and cholangiocarcinoma (CC) are less common but their prognoses are only marginally better. Patients with one of these cancers may undergo pancreaticoduodenectomy (PD) providing they present with resectable disease and have an appropriate performance status. Whilst this offers some patients the possibility of a cure, it is a high-risk operation and overall morbidity is often quoted at 50%. Additionally, early recurrence rates are high and few patients achieve long-term survival. This study aimed to describe the experience of a typical tertiary hepatopancreatobiliary (HPB) unit in the United Kingdom. We aimed to a compile a complication profile and investigate the impact of selected preoperative variables on short- and long-term outcomes. We also aimed to compare patient outcomes based on their cancer type. Methods: Patients were included if they underwent PD for histologically-confirmed PDAC, AA or CC at our institution between 01/09/2006 and 31/05/2015. The end date of 31/05/2015 was chosen to complete five-year follow-up for all included patients. Information was collected on the following: patient demographics, comorbidities, preoperative imaging and staging, NAT (if given), selected preoperative blood results, procedure and intraoperative findings, postoperative management and complications, histology results, adjuvant treatment (if given), cancer recurrence, palliative treatment (if given), and five-year survival. When comparing patients by their histological diagnosis, medians were compared using the Kruskal-Wallis test and other variables were compared using Fisher's exact test. Fisher's exact test was also used to investigate the association of selected preoperative variables on overall morbidity, major morbidity (Clavien-Dindo grade I and II complications excluded), 90-day mortality and five year survival. The Kaplan-Meier method was used to compare survival between patients with PDAC, AA and CC. The Mantel-Cox method was used to test for statistical significance. Fisher's exact test was used to investigate the impact of selected preoperative variables on five-year survival. A p-value of less than 0.05 was considered statistically significant. Results: A total of 271 patients were included; 57.9% had a histological diagnosis of PDAC, 25.8% had AA and 16.2% had CC. Ninety-day mortality was 3.3%, 67.9% of patients experienced at least one complication and 17.3% experienced a complication which was Clavien-Dindo grade III or higher. A total of 401 postoperative complications were recorded; 27.2% were CD grade I, 53.2% were grade II, 12.7% were grade III, 4.4% were grade IV and 1.5% were grade V. Rates of CR-POPF, bile leak, gastrojejunal leak, PPH and DGE were 8.1%, 4.1%, 0.0%, 9.2% and 19.9%, respectively. Patients with a preoperative bilirubin ≤29 µmol/L less often experienced morbidity (p=0.03) or major morbidity (p=0.02) but this did not affect 90-day mortality (p=0.7). Similarly, those with a preoperative neutrophil/lymphocyte ratio (NLR) ≤3.1 had lower rates of morbidity (p=0.04) and major morbidity (p=0.01) but the difference in 90-day mortality was not significant (p=0.3). An ASA grade of III or IV correlated with increased overall morbidity (p=0.002) and major morbidity (p=0.009) but the difference in 90-day mortality was not significant (p=0.2). Overall five-year survival was 22.5%; this was not affected by age, BMI, preoperative comorbidities, ASA grade or preoperative blood tests. Conclusions: In our series, most patients experienced at least one complication but less than a fifth experienced major morbidity. Rates of CR-POPF, bile leak, gastrojejunal leak, PPH and DGE were 8.1%, 4.1%, 0.0%, 9.2% and 19.9%, respectively. ASA grade III/IV patients and those with a high preoperative bilirubin and/or NLR more commonly experienced overall and major morbidity. Five-year recurrence and survival rates were 68.3% and 22.5%, respectively. The preoperative variables studied did not affect five-year survival. Surgeons who perform PD should have a sound understanding of the figures above as this will guide patient selection and the consenting process. Future research should focus on identifying patients who are likely to achieve poor long-term outcomes, this sub-group may benefit from neoadjuvant chemotherapy.